The Politeness Principles of Teachers and Students in English as a Foreign Language Classroom Interaction - Eva Anis Shofi`ah; Siti Aimah; Dodi Mulyadi (Universitas Muhammadiyah Semarang, 2017)
This study was conducted to find out the Politeness Principles in EFL classroom interaction. Consisting of six maxims; tact maxim, approbation maxim, generosity maxim, agreement maxim, modesty maxim and sympathy maxim. There were one English teacher and one classroom of eighth grade students of SMP Muhammadiyah 03 Semarang that became the subject of this study. Indepth, this study was to explore the use of politeness principles of students and teacher in the EFL classroom interaction. A mix method research with the domination of qualitative researchwas chosen as the research design. Classroom observation checklist, documentation, library research, were used as the instruments of the data collection. The result of the study shows that violation of politeness principles has the higher position with the percentage 41% rather than fulfillment with the percentage 31.5%, while other utterance becomes the lowest utterance with 27.5%. The highest maxim fulfilled was generosity with the percentage 38%, and the lowest maxim fulfilled was modesty maxim with 1%.